Analysis of Student Brawls in Junior High School 'X' Viewed from the Theory of Cultural Transmission - Nurhadiyanto, Lucky; Betauli, Martua; Rozak, Abdur (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Juvenile delinquency is a social problem that destroys the order of values that exist in society. Apart from that, juvenile delinquency can give unpleasant feelings to individuals or groups of people, such as feeling unsafe, life is not calm and peaceful and there is no peace. This research uses descriptive research methods with a qualitative approach. The analysis used in this research will use cultural transmission theory. This research uses data from literature studies, interviews and observations. This research was conducted for approximately 1 month in the South Jakarta area, precisely at SMP "X". The subjects chosen in this study were 3 teenagers who had already been involved in brawls. The background to student brawls between gangs is that there is a learning process that has made someone learn a deviant culture that exists in the social structure of society. Deviant cultural elements include dominant behavior and values held by group members which usually conflict with societal rules. Based on the results of interviews with informants A, B and C who are students from SMP "X" in South Jakarta, there are several factors that influence someone to take part in student brawls, namely emotional factors, family factors, and environmental factors both at home and school that support the student. to carry out brawls.